Analisis Efektivitas Pengendalian Internal Dengan Penerapan Stock Opname Pada PT Mahameru Centratama Spinning Mills - Canaya Fitrahnti Adinda; Astrini Aning Widoretno (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Stock opname is crucial for companies because it ensures the accuracy of inventory data, which is the basis for effective inventory management and informed decision-making. This study aims to find out whether the stock taking process allows companies to detect fraud, theft, or recording errors, so that the company's internal control can be said to be effective. The author uses a qualitative descriptive method in this study. The data collection method is carried out through interviews and observations. This research was conducted directly at PT Mahameru Centratama Spinning Mills to analyze the stock taking process on the company's asset inventory. The results of the study show that internal control with the implementation of stock taking at PT Centratama Spinning Mills is appropriate.